Concrete adaptation under extreme precipitation - Nicola Garbarino (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2025)
Does land development adapt to changing climate risks? Extreme precipitation increases flood risk, yet land-use decisions may overlook rare events. Drawing on nearly half a century of climate and land-use data for Europe (1975-2020), this paper finds that extreme precipitation slows the expansion of built-up areas, though only slightly. The effect is stronger over longer horizons, consistent with a clearer climate signal. Adaptation is concentrated in fast-growing urban areas. An accounting framework that combines these effects suggests that relocation in response to shifting precipitation patterns has reduced damages by roughly 5%.
Keywords: 330